A prospective randomized double-blind study comparing the dose-response curves of epidural ropivacaine for labor analgesia initiation between parturients with and without obesity - Huang, Xiao-Dong; Qiu, Xiao-Xiao; Wang, He-Jie; Jin, Xia-Fang; Xiao, Fei (Frontiers in Pharmacology, 2024)
Background Previous studies have explored the median effective concentration (EC50) of ropivacaine for labor epidural analgesia in parturients with obesity.However, the clinical relevance of the 90% effective concentration (EC90) remains unclear. This study aimed to determine and compare the dose-response curve of epidural ropivacaine for labor analgesia between parturients with and without obesity.Methods: Parturients were divided into two groups based on body mass index (BMI):group N, consisting of parturients with BMI <30 kg/m 2 , and group O, consisting of parturients with BMI >30 kg/m 2 . Within each group, the patients were randomized to receive one of five concentrations (0.0375%, 0.075%, 0.1125%, 0.15%, or 0.1875%) of epidural ropivacaine for labor analgesia. Analgesia was induced with a loading dose of 15 mL of the assigned concentration. Visual analogue scale (VAS) scores were recorded at baseline and 30 min post-dose to calculate the response (%) using the formula [(baseline VAS pain score -VAS pain score at 30 min)/baseline VAS pain score] ×100%. The EC50 and EC90 values were determined via nonlinear regression analysis.The EC50 and EC90 values of ropivacaine were 0.061% (95% confidence interval [CI], 0.056%-0.066%) and 0.177% (95% CI, 0.152%-0.206%) in group N and 0.056% (95% CI, 0.051%-0.061%) and 0.161% (95% CI, 0.138%-0.187%) in group O, respectively. No significant differences were observed in the EC50 and EC90 values between the two groups (P-values = 0.121 and 0.351, respectivelyIn conclusion, within the parameters of this study, our findings suggest that obesity, characterized by a mean BMI value of 30.9, does not significantly influence the EC50 and EC90 values of epidural ropivacaine for labor analgesia.Further investigations are warranted to elucidate the dose-response relationship between ropivacaine and obesity with higher BMI values.